Evaluation of GMP-compliant culture media for in vitro expansion of human bone marrow mesenchymal stromal cells - Wuchter, Patrick; Vetter, Marcel; Saffrich, Rainer; Diehlmann, Anke; Bieback, Karen; Ho, Anthony Dick; Horn, Patrick (Experimental hematology, 2016)
Mesenchymal stromal cells (MSCs) from human bone marrow serve as a resource for cell-based therapies in regenerative medicine. Clinical applications require standardized protocols according to good manufacturing practice (GMP) guidelines. Donor variability as well as the intrinsic heterogeneity of MSC populations must be taken into consideration. The composition of the culture medium is a key factor in successful MSC expansion. The aim of this study was to comparatively assess the efficiency of xeno-free human platelet lysate (HPL)-based cell expansion with two commercially available media - StemPro MSC SFM CTS (for human ex vivo tissue and cell culture processing applications) and MSCGM (non-GMP-compliant, for research only) - in an academic setting as the first optimization step toward GMP-compliant manufacturing. We report the feasibility of MSC expansion up to the yielded cell number with all three media. MSCs exhibited the typical fibroblastoid morphology, with distinct differences in cell size depending on the medium. The differentiation capacity and characteristic immunophenotype were confirmed for all MSC populations. Proliferation was highest using StemPro MSC SFM CTS, whereas HPL medium was more cost-effective and its composition could be adjusted individually according to the respective needs. In summary, we present a comprehensive evaluation of GMP-compatible culture media for MSC expansion. Both StemPro and HPL medium proved to be suitable for clinical application and allowed sufficient cell proliferation. Specific differences were observed and should be considered according to the intended use. This study provides a detailed cost analysis and tools that may be helpful for the establishment of GMP-compliant MSC expansion.
Gesehen am 01.07.2019